Empowering Future Mothers: A School Intervention Approach to Promote Breastfeeding Awareness among Adolescent Girls in Rural Uttar Pradesh, India - Kritika Tiwari; Priya Arora (Journal of Medical Academics)
Aims and background: Breastfeeding is vital for the health of both infants and mothers, yet breastfeeding rates remain low in rural areas of developing countries such as India. In rural Uttar Pradesh, sociocultural barriers and a lack of knowledge hinder optimal breastfeeding practices. This study aims to evaluate the effectiveness of a school-based educational intervention in promoting breastfeeding awareness among adolescent girls in this region. Materials and methods: This pre–post intervention study was conducted among adolescent girls from 7th to 12th grade at a government girls’ school in rural Uttar Pradesh. Stratified random sampling was used to ensure representative participation across different classes. A pretested, self-structured questionnaire assessed baseline knowledge, attitudes, and perceptions regarding breastfeeding. An interactive teaching session served as the intervention. Changes in knowledge, attitudes, and perceptions were measured using a posttest with the same questionnaire. Data were analyzed using the Statistical Package for the Social Sciences (SPSS) (version 23), with paired t-tests to compare pre- and posttest scores. Results: The mean pretest score was 6.05 [standard deviation (SD) = 2.01], which significantly increased to 11.26 (SD = 1.46) postintervention (p < 0.001). The effect size (Cohen's d) was 2.1, indicating a very large impact. Positive attitudes toward breastfeeding increased from 87.1 to 98.4%, and future breastfeeding intentions rose from 79 to 96.8%. The majority of participants (68%) were initially unaware of breastfeeding week, and family was the most common source of breastfeeding knowledge. Conclusion: The school-based educational intervention significantly improved breastfeeding knowledge and attitudes among adolescent girls in rural Uttar Pradesh. This suggests that such interventions can effectively address knowledge gaps and misconceptions, providing a supportive environment for future breastfeeding practices. Clinical significance: Educational interventions in schools can play a crucial role in promoting breastfeeding awareness and positive attitudes among future mothers in rural areas. Implementing similar programs could enhance breastfeeding practices, thereby improving maternal and child health outcomes in resource-limited settings.